Effects of Probiotic Treated Pomegranate Residue on Growth Performance, Immunity and Microbiome in the Intestines of Broilers - Ahmed, Sonia T.; Mun, Hong-Seok; Yang, Chul-Ju (International Journal of Poultry Science, 2025)
Objectives: This research was undertaken to assess the effect of probiotic treated pomegranate residue (PPR) on growth performance, serum immunoglobulins, intestinal and excreta microbiome, and excreta harmful gas emission in broilers. Materials and Methods: A total of 128 day-old Ross-308 chicks were randomly assigned to 4 treatment groups, each consisting of 4 replicates of 8 birds. The experimental diets were formulated to supply 0, 0.5, 1.0 and 2.0% of PPR and were fed for 35 day. Results: Dietary inclusion of PPR linearly increased the weight gain of broiler, while reduced FCR by almost 0.10 points without affecting the feed intake (p<0.05). Following the addition of PPR, a linear rise in serum IgA concentration was perceived (p<0.05). Dietary PPR increased the ileal and cecal Lactobacillus, cecal Bacillus (linear, p<0.05) and ileal yeast and mold (linear, p = 0.0007; quadratic, p = 0.007) population. In contrary, the E. coli population has been decreased in the ileal (linear, p = 0.004, quadratic, p<0.04) and cecal digesta (linear, p = 0.004) and Salmonella only in the cecal digesta (linear, p = 0.0004) in consequence of dietary PPR. As the dose level increased PPR linearly reduced the ileal and cecal pH (p<0.05). Dietary PPR increased the CFU of excreta Lactobacillus (linear, p = 0.002) and Bacillus (quadratic, p<0.05), whereas, decreased the E. coli population (linear, p = 0.008). In relation to dietary PPR supplementation, excreta pH was linearly lowered (p<0.05). Inclusion of 1% and 2% PPR reduced the NH3 and H2S emission from broiler excreta. Conclusion: Therefore, it can be concluded that PPR supplemented up to 2% level may improve the growth performance, immunity and microbiome in the intestines of broilers.